PEMANFAATAN LIMBAH PLASTIK MIKA SEBAGAI ALAT PERAGA MANIPULATIF PADA MATERI PECAHAN - Dina Pratiwi Dwi Santi; Setiyani Setiyani; Ena Suhena Praja Riyanti (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2022)
The use of manipulative teaching aids becomes a must when teachers explain mathematical concepts to students at the elementary school level (SD). Teaching aids can bridge the thinking patterns of elementary school students who are still in the concrete operational stage and abstract mathematical concepts. The purpose of this Community Service (PKM) activity is to provide training by utilizing waste such as mica plastic as manipulative teaching aids to explain concepts at One Roof Source Elementary School. The methods in this service activity are question and answer, demo and simulation. The flow or stages of service activities begin with an initial survey, coordination, implementation of training, evaluation, and preparation of reports. The results of the training on the use of mica plastic as manipulative teaching aids include increasing teacher knowledge regarding materials that can be used as teaching aids. In addition, the number of participants who attended was in accordance with the target, there was a positive response from participants in using mica/waste plastic as manipulative props, enthusiasm and interest in activity participants. As a recommendation, the team will design teaching aids from other waste that are attractive, varied, inexpensive, and easy to obtain as an effort to improve the quality of learning and teacher professionalism. Penggunaan alat peraga manipulatif menjadi sebuah keharusan ketika guru menjelaskan konsep matematika pada siswa di jenjang Sekolah Dasar (SD). Alat peraga dapat menjembatani pola berpikir siswa SD yang masih dalam tahap operasional konkrit dan konsep matematika yang bersifat abstrak. Tujuan kegiatan Pengabdian Kepada Masyarakat (PKM) ini adalah memberikan pelatihan dengan memanfaatkan limbah seperti plastik mika sebagai alat peraga manipulatif untuk menjelaskan konsep pecahan di SDN Satu Atap Sumber. Metode dalam kegiatan pengabdian ini yaitu tanya jawab, demonstrasi dan simulasi. Adapun alur atau tahapan kegiatan pengabdian diawali dengan survey awal, koordinasi, pelaksanaan pelatihan, evaluasi, dan penyusunan laporan. Hasil dari pelatihan pemanfaatan plastik mika sebagai alat peraga manipulatif diantaranya menambah pengetahuan guru terkait bahan yang dapat dimanfaatkan sebagai alat peraga. Selain itu jumlah peserta yang hadir sesuai dengan target, adanya respons positif peserta dalam memanfaatkan plastik mika/limbah sebagai alat peraga manipulatif, antusiasme dan ketertarikan peserta terhadap kegiatan pelatihan. Sebagai rekomendasi tim akan merancang alat peraga dari limbah lainnya yang menarik, variatif, murah, dan mudah didapatkan sebagai upaya peningkatan kualitas pembelajaran dan profesionalisme guru.